Regional health inequalities in Karnataka: translating NFHS-5 evidence into better district health planning - Naikar, Suvarna K.; Channakki, H. R. (International Journal Of Community Medicine And Public Health, 2026)
Background: Karnataka, one of India’s most socio-economically diverse states, exhibits considerable regional inequalities in health outcomes. Northern districts consistently lag behind southern districts in socio-demographic development and maternal and reproductive health indicators. These inequalities reflect the effectiveness of local policy implementation. The study assesses district and regional-level inequalities in socio-demographic and maternal and reproductive health indicators across Karnataka and identify priority districts for targeted health planning and resource allocation. Methods: District-level data from National Family Health Survey (NFHS-5) (2019-21) were analyzed. Indicators were aggregated into four administrative divisions using weighted averages. Composite Health Index (CHI) scores were calculated for socio-demographic and maternal and reproductive health dimensions. Regional inequalities were examined using descriptive statistics, quartile deviation, and district-level rankings, and spatial mapping in QGIS. Results: Districts with higher female education, improved sanitation, access to clean cooking fuel, and health insurance coverage achieved higher socio-demographic CHI scores and better maternal and reproductive health outcomes. Northern districts, including Kalaburagi, Yadgir, Raichur, Koppal, and Vijayapura recorded comparatively lower CHI scores, while southern districts performed better across most indicators. Significant intra-divisional variation highlighted substantial inequalities within administrative regions. Conclusions: Persistent regional inequalities in Karnataka are driven by adverse social determinants of health and unequal access to maternal healthcare services. Region-specific interventions focusing on female education, sanitation, gender equity, and strengthened maternal health services are essential to reduce inequalities and improve maternal and reproductive health outcomes across the state.